THEORETICAL AND APPLIED UNDERSTANDING OF QUALITY ASSURANCE OF FINANCIAL INNOVATIONS IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT DURING MILITARY CHALLENGES (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. It is investigated that financial technologies are considered to be one of the most important innovations in the financial industry, as they reflect the growth of the technological industry and the effective cross-sectoral integration. It is established that financial development is a necessary component of economic growth, and a well-functioning financial system contributes to economic prosperity. It has been investigated that financial innovations, as well as elements, such as research and development costs, technology transfer, are recognized as important factors that contribute to financial innovation. It is analyzed that financial innovations arise as a result of the costs of research and innovation, technologies and networks. It is investigated that the socio-oriented process of economic development aims at ensuring economic and social security, as well as the effective reproduction of natural resources.The purpose of the article. It is necessary to investigate the theoretical and applied understanding of the quality of financial innovations in the context of sustainable development during military challenges.Results. Financial innovations play a significant role in promoting economic growth through the introduction of new financial products. They contribute to the effective use of business resources through simplified financial transactions and reducing potential losses. Financial innovations occur as a result of investments in research and innovation activities, technologies and networks. New financial products, improved payment methods, reducing investment risks and accelerating capital accumulation are just a few examples of financial innovations.Conclusions. There are a number of measures to improve financial development. One of them is to improve bank lending, which will increase access to financial resources. To achieve sustainable development goals, it is necessary to create a competitive environment where all market participants will have equal access to information. This means that you need to ensure transparency of information and eliminate any obstacles to obtain it. In addition, it is important to continuously improve the technical infrastructure, which will provide quick and reliable access to financial services. Financial innovation and quality of institutions are an integral part of financial markets development.
Keywords: financial development, financial innovations, digitization, sustainable development, military challenges.